The Portuguese Disabled People's Movement: development, demands and outcomes - Fontes, Fernando (2014)
The increased variety of social conflicts in the post-1960 years resulted in the extension of the individual’s participation in the state’s activity. This change was mirrored by the emergence of new social movements and the related expansion of the notion of citizenship. New groups of people, including disabled people, have emerged claiming citizenship rights. In order to do this, disabled people started to coalesce into uni-impairment and multi-impairment groups and organisations to denounce social exclusion and legal oppression, as well as to demand rights as citizens. Partially based on my research about social citizenship and the Disabled People’s Movement, this article investigates, firstly, the seeds and development of the Portuguese Disabled People’s Movement, secondly, its aims, demands and action strategies and, finally, its impact in the lives of disabled people in Portugal.